Effect of abdominal massage on feeding intolerance in patients receiving enteral nutrition: A systematic review and meta‐analysis - Jia Wang; Yahong Chen; Hui Xue; Zhiming Chen; Qiuchen Wang; Mingyue Zhu; Jiannan Yao; Hua Yuan; Xiuying Zhang (Nursing Open, 2023)
Abstract Aim This study aimed to evaluate the effect of abdominal massage (AM) on feeding intolerance (FI) in patients receiving enteral nutrition (EN). Design A systematic review and meta‐analysis. Methods We searched seven electronic databases to September 2021. STATA and RevMan were used to analyse the data. Results Eleven studies were included. The results revealed that AM could significantly reduce gastric residual volume and abdominal circumference difference, and reduce the incidence of gastric retention, vomiting, abdominal distention (all p < 0.001), diarrhoea (p = 0.02) and constipation (p = 0.002) in the experimental group. One study reported the incidence of aspiration in the control group was higher, but this was not statistically significant (p = 0.07). The meta‐regression analysis showed there was a statistically significant correlation between intervention personnel and gastric residual volume (p = 0.035). Conclusion AM could reduce the amount and incidence of gastric retention and the changes in abdominal circumference, and significantly reduce the incidence of gastrointestinal symptoms, without increasing the incidence of aspiration for EN patients. No Patient or Public Contribution.